Differences in the Linguistic Features of Text Messages send with an Alphanumeric Multi-Press Keypad Mobile Phone versus a Full Keypad Touchscreen Smartphone - Kent, Sarah; Johnson, Genevieve (Scottish Group of Education and Testing Services, 2012)
Technology often mediates, and thus influences, patterns of human communication. Mobile phones have recently improved, most notably, full keypad touchscreen smartphones. Fifty university students send text messages with a traditional multi-press alphanumeric keypad mobile phone and a full keypad touchscreen smartphone. Compared to messages sent via multi-press mobile phones, smartphone messages where longer, contained fewer number/letter homophones (e.g., cu rather than see you) and contained more punctuation and fewer misspelled words. Nonetheless, regardless of type of phone used, text messages evidenced use of the language form known as digitalk or textese, suggesting that keypad limitations cannot entirely explain the unique patterns of written communication associated with mobile phones.